Breach of IEPS’ non-tax purposes to pesticides in Mexico - Gutiérrez Jiménez, Itzel (2026)
Non-tax purposes of taxes pretend to cause behaviors on contributors. One way to analyze its functioning is examining its collection trough time, be- cause it is assumed that if the amount of collection decreases is because of the effectivity of the non-tax purpose. In Mexico there is a tax for sales of pesticides, which is regulated in Special Tax on Production and Services —named in Mexico as “Impuesto Especial sobre Produccion y Servicios” (IEPS)—, and its non-tax purpose es to decrease the consumption of those products. This paper analyses if during 2014 to 2023 that objective has been achieved, therefore that could be seen as a decrease in using, producing and selling pesticides, and in a lack of collection of this tax. Results show that, contrary to expectations, indicators increased during the period analyzed, therefore considering this analysis non-tax purpose has not been achieved. Absence of an official evaluation does not allow a technical discussion to modify this tax to achieve its objectives.